2022
DOI: 10.1002/jbt.23083
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid‐induced oxidative damage and endoplasmic reticulum stress‐mediated apoptosis in human embryonic kidney (HEK‐293) cells

Abstract: Zoledronic acid, a nitrogen‐containing bisphosphonate drug, is used for the treatment of osteoporosis, Paget's disease of bone, and tumor‐induced osteolysis. Zoledronic acid has also gained a place in cancer treatment due to its cytotoxic and antiproliferative effects in many cancer cells. Although zoledronic acid is considered safe, kidney damage is still one of the concerns in therapeutic doses. In the study, the aim was to assess the nephrotoxic profiles of zoledronic acid in the human embryonic kidney (HEK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 83 publications
2
7
0
Order By: Relevance
“…Zoledronic acid is a potent inducer of reactive oxygen species and DNA damage, which is clinically used to sensitize cancer cells prior to radiotherapy [38,56]. In accordance with other studies [56,62,63,75], we also detected a dose-dependent increase in DNA strand breaks and H2A.X phosphorylation in the ZOL-treated PdL fibroblasts, pointing to enhanced levels of DNA damage. Increased H2A.X phosphorylation levels are also often associated with cellular senescence [66].…”
Section: Discussionsupporting
confidence: 91%
“…Zoledronic acid is a potent inducer of reactive oxygen species and DNA damage, which is clinically used to sensitize cancer cells prior to radiotherapy [38,56]. In accordance with other studies [56,62,63,75], we also detected a dose-dependent increase in DNA strand breaks and H2A.X phosphorylation in the ZOL-treated PdL fibroblasts, pointing to enhanced levels of DNA damage. Increased H2A.X phosphorylation levels are also often associated with cellular senescence [66].…”
Section: Discussionsupporting
confidence: 91%
“…As the duration of exposure to MW increased, a corresponding decrease in the absorption values was recorded after treatment with 200 μg/mL MgFe 2 O 4 ( Figure S4C ). It was found that both MgFe 2 O 4 , ZOL, and MW can stimulate ROS production as previously reported [ 66 , 67 ].
Fig.
…”
Section: Resultssupporting
confidence: 84%
“…Generally, VERO and HEK-293 cells have shown ways to deal with generated ROS from some external source. Several research findings revealed that ROS are not lethal to VERO or HEK-293 cells at lower concentrations 57 , 58 . However, if the concentration is above a certain threshold, then these AgONPs are detrimental 59 .…”
Section: Resultsmentioning
confidence: 99%